Influence of the early stimulation in the psychomotor development of infants - Magalis Puente Perpiñan; Aritza Suastegui Pando; Meibol Leydi Andión Rente; Lisbet Estrada Ladoy; Alina de los Reyes Losada (Centro Provincial de Información de Ciencias Médicas, 2020)
Introduction: The early stimulation is the group of actions that are offered to a boy or girl in the first years of life to avoid delay in the psychomotor development.   Objective: To evaluate the impact of the early stimulation in the psychomotor development of infants.  Methods: An observational, descriptive and prospective study of 60 infants with early stimulation was carried out, they were assisted by the 1 Work Basic Group, belonging to the health area of Camilo Torres Restrepo in Santiago de Cuba, from June, 2016 to the same period in 2018.  Results: There was a prevalence of the male sex (32 for 53.4 %) and the 1 to 3 months age group (48 for 80 %). The prenatal record with more negative was the deficiency anemia present in 36 mothers (60.0 %) and the low apgar, as natal record, was found in 17 infants (28.3 %), being necessary the oxygen use in 20 of them (33.3 %). The main disorders presented were the torticollis (25 for 41.6 %) and the hypotonia (23 for 38.3 %). Most of the patients had a favorable clinical course (54 for 90.0 %).  Conclusions: The impact of the early stimulation in the psychomotor development was positive, because the favorable clinical course of the infants was achieved.